Relations of power and oppression within the delivery room: nursing narratives - Rangel-Flores, Yesica Yolanda; Martínez-Villa, Consuelo Magdalena; Jiménez-Arroyo, Vanesa (Revista da Escola de Enfermagem da USP, 2022)
Objective: To analyze, from the perspective of decolonial feminism, the power and oppression relations experienced by nurses in the delivery room in a hospital in Mexico. Method: Qualitative study in which 15 nurses selected by theoretical sampling were interviewed. The interviews were fully transcribed and subsequently analyzed using content analysis. Results: The emerging central category was “Inter- and intragender power/oppression relations” and psychological and symbolic violence were the most frequent types. Gender was confirmed as the most important structural determinant of oppression, cutting across bodies and professional identities. The conditions contributing to intragender conflict are age, expertise, and specialization. Three coping resources were documented: defenselessness, complicity and resistance. Conclusion: It is necessary to denaturalize the forms of power/oppression sustained by gender inequalities, but also to discuss other conditions that determine power/oppression relations between women and colleagues. Eradicating intra-gender and intergender violence is necessary to access safe working environments that promote creativity for the exercise of care.